Paying to Be Nice: Consistency and Costly Prosocial Behavior - Gneezy, Ayelet; Imas, Alex; Brown, Amber; Nelson, Leif D.; Norton, Michael I. (Management Science, 2012)
Building on previous research in economics and psychology, we propose that the costliness of initial prosocial behavior positively influences whether that behavior leads to consistent future behaviors. We suggest that costly prosocial behaviors serve as a signal of prosocial identity and that people subsequently behave in line with that self-perception. In contrast, costless prosocial acts do not signal much about one's prosocial identity, so subsequent behavior is less likely to be consistent and may even show the reductions in prosocial behavior associated with licensing. The results of a laboratory experiment and a large field experiment converge to support our account. This paper was accepted by Brad Barber, Teck Ho, and Terrance Odean, special issue editors.